Indonesia’s Policy on the Import Ban of Second-Hand Clothing from the Perspective of the Principles of Non-Discrimination and National Treatment - Maghfiroh, Laily (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study examines the legal issue of whether Indonesia’s policy banning the import of used clothing is consistent with the WTO Non-Discrimination principles, namely the Most Favoured Nation and National Treatment obligations under GATT 1994. This issue is significant because Indonesia prohibits imported used clothing on the grounds of protecting public health and maintaining trade order, while domestically sourced used clothing remains permitted, raising concerns of unequal treatment toward foreign products. The research employs a normative juridical method through a statutory approach by analyzing the Trade Law, relevant Ministry of Trade regulations, and customs provisions, as well as a conceptual approach to assess the application of WTO principles. Legal materials were gathered through library research and analyzed qualitatively. The findings show that the import ban does not violate the Most Favoured Nation principle because it applies uniformly to all WTO members. However, the policy potentially conflicts with the National Treatment obligation since similar domestic products are still allowed to circulate. Nevertheless, GATT provides justification through Article XX if Indonesia can demonstrate that the ban is necessary to protect public health and consumer safety. The study concludes that Indonesia’s ability to defend the policy depends on meeting the necessity test, presenting scientific evidence, and ensuring consistent enforcement to avoid being perceived as protectionist.